Body Mass Index and Risk of Cardiovascular Disease, Cancer and All-cause Mortality - Katzmarzyk, Peter T. (Can J Public Health, 2012)
Objectives: To determine the dose-response relationship between body mass index (BMI) and cause-specific mortality among Canadian adults. Methods: The sample includes 10,522 adults 18–74 years of age who participated in the Canadian Heart Health Surveys (1986–1995). Participants were divided into 5 BMI categories (<18.5, 18.5–24.9, 25–29.9, 30–34.9, and =35 kg/m(2)). Multivariate-adjusted (age, sex, exam year, smoking status, alcohol consumption and education) hazard ratios for all-cause, cardiovascular disease (CVD) and cancer mortality were estimated using Cox proportional hazards regression. Results: There were 1,149 deaths (402 CVD; 412 cancer) over an average of 13.9 years (range 0.5 to 19.1 years), and the analyses are based on 145,865 person-years. The hazard ratios (95% CI) across successive BMI categories for all-cause mortality were 1.25 (0.83–1.90), 1.00 (reference), 1.06 (0.92–1.22), 1.27 (1.07–1.51) and 1.65 (1.29–2.10). The corresponding hazard ratios for CVD mortality were 1.30 (0.60–2.83), 1.00 (reference), 1.57 (1.22–2.01), 1.72 (1.27–2.33) and 2.09 (1.35–3.22); and for cancer, the hazard ratios were 1.02 (0.48–2.21), 1.00 (reference), 1.14 (0.90–1.44), 1.34 (1.01–1.78) and 1.82 (1.22–2.71). There were significant linear trends across BMI categories for all-cause (p=0.0001), CVD (p<0.0001) and cancer mortality (p=0.003). Conclusions: The results demonstrate significant relationships between BMI and mortality from all causes, CVD and cancer. The increased risk of all-cause, CVD and cancer mortality associated with an elevated BMI was significant at levels above 30 kg/m(2); however, overweight individuals (BMI 25–29.9 kg/m(2)) also had an approximately 60% higher risk of CVD mortality.